2005
DOI: 10.1103/physrevb.72.020101
|View full text |Cite|
|
Sign up to set email alerts
|

Ferroelectricity in ultrathin perovskite films

Abstract: We report studies of ferroelectricity in ultra-thin perovskite films with realistic electrodes. The results reveal stable ferroelectric states in thin films less than 10Å thick with polarization normal to the surface. Under short-circuit boundary conditions, the screening effect of realistic electrodes and the influence of real metal/oxide interfaces on thin film polarization are investigated. Our studies indicate that metallic screening from the electrodes is affected by the difference in work functions at ox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(135 citation statements)
references
References 17 publications
(20 reference statements)
6
128
0
Order By: Relevance
“…The presence of interfaces imposes restrictions on the atomic displacements since the atoms at the boundary of the FE are bonded to the electrodes. This effect was demonstrated in KNbO 3 FE films placed between SrRuO 3 or Pt electrodes [160], as well as BaTiO 3 with SrRuO 3 [161,162], Fe [116] and Pt [163] electrodes. First-principles transport calculations for Pt/BaTiO 3 /Pt FTJs show that the interface transmission function [164] of the Pt/BaTiO 3 interface differs by a factor of three depending on the polarization direction [159].…”
Section: (A) Ferroelectric Tunnel Junctionsmentioning
confidence: 93%
“…The presence of interfaces imposes restrictions on the atomic displacements since the atoms at the boundary of the FE are bonded to the electrodes. This effect was demonstrated in KNbO 3 FE films placed between SrRuO 3 or Pt electrodes [160], as well as BaTiO 3 with SrRuO 3 [161,162], Fe [116] and Pt [163] electrodes. First-principles transport calculations for Pt/BaTiO 3 /Pt FTJs show that the interface transmission function [164] of the Pt/BaTiO 3 interface differs by a factor of three depending on the polarization direction [159].…”
Section: (A) Ferroelectric Tunnel Junctionsmentioning
confidence: 93%
“…Correspondingly, in the beginning of XXI century the main model for ferroelectric screening has become external screening by surface ionic charges, as explored by SPM, 74,76 X-ray 78,228 and density functional theory. 235 The direct visualization of the mobile surface charges was performed using time-resolved Kelvin Probe Microscopy. 236,237 The necessary consequence of the ionic screening model is that polarization switching necessitates the redistribution of the screening charges, and overall polarization dynamics is now controlled both by ferroelectric and ionic subsystems.…”
Section: A Surface Ionic Screeningmentioning
confidence: 99%
“…1 A FTJ consists of two metal electrodes separated by a nm-thick ferroelectric barrier which allows electron tunneling through it. Recent experimental 2-4 and theoretical [5][6][7][8] studies of perovskite ferroelectric oxide thin films have demonstrated that ferroelectricity persists down to a nanometer scale, which makes it possible to use ferroelectrics as functional tunnel barriers in FTJs. Contrary to ferroelectric capacitors where leakage currents are detrimental to the device performance, 9 the conductance of a FTJ is the functional characteristic of the device.…”
Section: Introductionmentioning
confidence: 99%